The Implementation of Theory of Planned Behavior towards Intention of Using Quick Response Code Indonesian Standart among Students - Pratita, Mutya Paramita; Sumaryanto, Sumaryanto; Zakiyah, Nadiya Fikriyatuz (Dinasti Publisher, 2025)
Technology continues to evolve, demanding society to adapt to its advancements, particularly in payment methods where cashless transactions are increasingly prevalent. One such cashless payment method is QRIS (Quick Response Code Indonesian Standard), which aims to facilitate transactions between consumers and merchants for greater convenience. A primary target of this method is Generation Z, specifically university students. It is crucial for sellers to understand students' interest in adopting QRIS as a payment method. To achieve this goal, this study employed a questionnaire distributed randomly among a population of university students in Surakarta, with a sample size of 100 respondents. Data analysis was conducted using SmartPLS, and the results indicate that subjective norms have no effect on the intention to use QRIS, while other variables within the Theory of Planned Behavior (TPB) show a positive influence when mediated by trust in QRIS.